(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This study focuses on the relationship between parent’s socioeconomic status and student’s academic performance in different graduate and undergraduate programs offered by constituent colleges of Pokhara University. The total sample of the present study was 301 students who have been pursuing their respective academic degrees. The sampling design was based on a purposive convenient method. Structured questionnaire technique was used to obtain quantitative data related to parental socio – economic status and academic performance of students. The results revealed that parental socio - economic status and parent’s level of education does not have a significant relationship with academic performance of students. However, the occupation of parents has a greater impact on academic performance of students. Moreover, the residence of the students has a significant impact on the academic performance of the students. The findings of the study also reveal that family financial status is more important determinant of school level academic grades, however, its influence in college level grades is relatively low. Although, parent’s educational status is found to be associated with academic achievement, father’s employment nature and family expenditure level were found to be the most significant determinants of academic achievement of students. However, the relationship is true only up to the school level academic performance. यो अध्ययनले पोखरा विश्वविधालय अन्र्तगतका विभिन्न कलेजहरुले संचलान गरेका स्नातकोत्तर तथा स्नातक कार्यक्रमका अभिभावकहरुकोसामाजिक आर्थिक स्थिति र विद्यार्थीहरुको शैक्षिक उपलब्धि बीचको सम्बन्धलाई उजगर गरेको छ । यस अनुसंधानको लागि अहिले पढदै गरेका३०१ विद्यार्थीहरुलाई छनौट गरिएको थियो । यस खोजका नमूना विद्यार्थीहरु परपोशिभ कनभेनियन्ट (उद्देशयपरक सुविधाजनक) विधिबाट छनौटगरिएको थियो । साथै अभिभावकहरुको सामाजिक आर्थिक स्थिति र विद्यार्थीहरुको शैक्षिक उपलब्धिसंग समबन्धित गुणात्मक तथ्यांकहरुस्टरचकर कोइशनारहरु (संरचनात्मक प्रश्नावली) विधिको प्रयोग गरेर संकलन गरिएको थियो । यस अध्ययनले अभिभावकहरुको सामाजिकआर्थिक स्थिति तथा अभिभावकहरुको शैक्षिक स्तरले विद्यार्थीहरुको शैक्षिक उपलब्धिमा खाखै असर नपार्ने देखाँउछ । यदपि अभिभावकहरुकापेशाले विद्यार्थीहरुको शैक्षिक उपलब्धिमा ठूलो प्रभाव पार्छ । यसबाहेक विद्यार्थीहरुको बसोबासले विद्यार्थीहरुको शैक्षिक उपलब्धिमा ठूलोप्रभाव पार्छ । यस अनुसंधानले यो पनि देखाँउछ कि परिवारको आर्थिक अवस्थाले विद्यार्थीको कलेज स्तरको शिक्षा भन्दा विधालय स्तरकोशिक्षामा महत्वपूर्ण भूमिका खेल्छ । यद्दपि अभिभावकको शैक्षिक स्थिति विद्याथीको शैक्षिक उपलब्धिसँग जोडिएको छ , बुवाको रोजगारीप्रकृति र पारिवारिले र्खच गर्ने क्षमताले विद्यार्थीको विधालय स्तरको शैक्षिक उपलब्धिमा निर्णयक भूमिका खेल्छ ।